Behavioral Versus Nonbehavioral Guided Self-Help for Parents of Children With Externalizing Disorders in a Randomized Controlled Trial. Issue 6 (November 2018) - Hautmann, Christopher; Dose, Christina; Duda-Kirchhof, Karin; Greimel, Lisa; Hellmich, Martin; Imort, Stephanie; Katzmann, Josepha; Pinior, Julia; Scholz, Kristin; Schürmann, Stephanie; Wolff Metternich-Kaizman, Tanja; Döpfner, Manfred
Abstract: Self-help interventions for parents, which have a behavioral basis, are considered to be an effective treatment option for children with externalizing disorders. Nonbehavioral approaches are widely used but have little empirical evidence. The main objective of this trial was to compare the efficacy of a behavioral and a nonbehavioral guided self-help program for parents. Families of children (aged 4–11 years) diagnosed with attention-deficit/hyperactivity disorder (ADHD) or oppositional defiant disorder (ODD) were randomized to either a behavioral or a nonbehavioral guided self-help program including 8 parenting booklets and 10 counseling telephone calls. The analyses considered the ratings of 5 informants: blinded clinician, therapist, participant, (her or his) partner, and teacher. Of the 149 families randomized to treatment (intention-to-treat sample [ITT]), 110 parents completed the intervention (per-protocol sample [PP]). For the 4 primary outcome measures (blinded clinician- and participant-rated ADHD and ODD) at post-assessment, the analysis revealed a treatment advantage for the behavioral group in blinded clinician-rated ODD symptoms (ITT: d = 0.37; PP: d = 0.35). Further treatment differences, all in favor of the behavioral group (ITT and PP), were detected in therapist ratings (i.e., ODD) and participant ratings (e.g., parental self-efficacy [only PP], negative parenting behavior, parental stress). In both samples, no differences were found at post-assessment for ratings of the partner and the teacher, or at the 12-month follow-up (only participant ratings available). Behavioral guided self-help shows some treatment advantage in the short term. No superiority over nonbehavioral therapy was detected 12 months after treatment termination. Highlights: Guided self-help for parents may reduce child externalizing behavior. Guided self-help may be a viable addition to already fully established forms of psychotherapy. Parents receiving behavioral-based self-help may have some short-term advantage. Dropout rates are comparable to those found for face-to-face parent training.